Features of river flow in inland valleys in semi-deciduous forest zone in Ghana - Fujii, H.; Dawuni, B.; Kulawardhana, Wasantha; Thenkabail, Prasad S.; Namara, Regassa E. (2009)
There are about 2.8 million ha of inland valleys in Ghana and 20 million ha of inland valley in West Africa. Although inland valleys are suitable for lowland rice due to the abundance of water resources and higher soil fertility compared with the upland, they have not been well utilized as agricultural land in West Africa. Further utilization of inland valley for lowland rice will improve the productivity of rice in West Africa. In this study water resources of small rivers in inland valleys in West Africa are evaluated. Two study watersheds with 1,400-1,500mm of annual rainfall in Semi-Deciduous Forest Zone in Ghana were selected and analyzed on slope distribution in the study watershed to grasp suitable area for lowland rice and on hydrological characteristics such as specific discharge and runoff ratio. The following findings are obtained from the study. 1) Most of the rivers in the study watershed are seasonal rivers. Non-flow period of some rivers were shown for around five months from middle of December to early May. However the term of non-flow period varies much depending on characteristics of sub-watersheds. 2) Runoff ratio for 5 years from 2000 to 2004 in Offinso watershed which is a typical watershed in semi deciduous forest zone in Ghana was indicated only 12%. It ranges from 0.08 to 0.16 depending on the year. The monthly runoff ratio indicated little value in March, April and May which is beginning of rainy season and high value in November and December which is beginning of dry season. 3) The gentle slope area with less than 2%, which seems suitable area for lowland rice, occupies 22 % of inland valley.